Lung cancer in situs inversus totalis (SIT) – a case report - Wójcik, Janusz; Kubisa, Bartosz; Pieróg, Jarosław; Bielewicz, Michał; Wójcik, Norbert; Kaseja, Krzysztof; Grodzki, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
A case of a 69-year-old patient with bronchogenic large cell cancer of the left lung and metastatic tumor in the right suprarenal gland associated with situs inversus totalis (SIT) is presented. The patient underwent left thoracotomy and laparoscopy with the option of adjuvant chemotherapy afterwards. The SIT diagnosis was based on bronchofiberoscopy, contrast enhanced chest computed tomography and echocardiography as well. At the time of both operations the mirror image anatomy was confirmed. This is the second SIT case treated surgically at the authors’ department.